Potential for Transition to a Polygynous-Supercolonial Demography in Lasius niger (Hymenoptera, Formicidae) - S. Stukalyuk (Zoodiversity, 2025)
The formicine ant, Lasius niger (Linnaeus, 1758), is one of the most abundant and intensively studied Palaearctic ant species, and was previously thought to form exclusively monogynous colonies, spread by single-queen dispersal, and occur claustrally. Two closely neighboring nest complexes of L. niger were observed in 2017–2020 in an abandoned field near Kyiv / Ukraine. Nest complex A contained 14650 nest mounds on an area of 11.8 ha and nest complex B contained 15600 mounds on an area of 13.3 ha. Data were collected by measuring the height and diameter of nest mounds and counting the number of workers in each nest. In addition, worker movements between nests were observed and tests for aggressive behaviour between ants from different nests and sub-complexes were carried out. In the pleometrosis experiments, young mated gynes collected from the territory of nest complex B showed mutual tolerance after the first workers emerged from pupae. In contrast, in pleometroses with gynes from a distant monodomous population, the gynes began a deadly fight after workers emerged, with only a single queen surviving. Nest mounds within nest complexes are connected by a well-developed network of trails. The results of the analysis showed a positive correlation between nest size and population size. The coefficient of determination r2 for nest mound volume was 0.68415, indicating that 68.4 % of the variation in population size was explained by changes in nest mound volume. In comparison, r2 for nest mound diameter was 0.7872, meaning that 78.7 % of the variation in population size was explained by changes in nest mound diameter, while r2 for nest mound height was 0.42734, meaning that only 42.7 % of the variation in population size was explained by changes in nest mound height. Observations of worker movements revealed a high degree of organisation and specialisation, helping to maintain connections between nest mounds. Aggression tests revealed low levels of aggression between workers from different zones of the same nest complex, but increased aggression in confrontations between workers from a nest complex with workers from a remote monodomous population and with workers from a second nest complex. Pleometrosis and reduced aggression between workers facilitate the integrity of the nest complex and its rapid growth. Based on the data obtained, it was concluded that the low aggressiveness of L. niger ants allows them to coexist over large areas in the form of large nest complexes containing thousands and tens of thousands of nest mounds. Additional auxiliary nests were identified that may become new full-scale nest mounds in the future, indicating a potentially higher settlement density than if only nest mounds were considered.